Chinese herbal medicine anticancer cocktail soup activates immune cells to kill colon cancer cells by regulating the gut microbiota-Th17 axis - Nie, Xiaoli; Geng, Zixiang; Liu, Jianjun; Qi, Li; Wang, Zetian; Liu, Te; Tang, Jianguo (Frontiers in Pharmacology, 2022)
Colon cancer (CC) is a highly malignant tumor of the digestive tract. Multiple studies have noted that Chinese herbal medicine has substantial therapeutic efficacy in CC. Meanwhile, it has been reported that the occurrence of CC is greatly associated with abnormalities of the structure and species of gut microbiota, and the dysregulation of immune function. Here, we explored the therapeutic effects of Chinese herbal medicine anti-cancer cocktail soup (CHMACS) on CC-bearing mice, as well as its regulatory action on the gut microbiota. In vivo experiments show that CHMACS significantly inhibited the proliferation and tumorigenicity of CC cells in mice. Also, CHMACS decreased the numbers of CD8+ T, NK, and Th17 cells. HPLC/MS analysis showed that CHMACS comprises 227 components. 16S sequencing revealed that the relative abundance of uncultured_bacterium_g_Turicibacter increased, but uncultured_bacterium_g_Coriobacteriaceae_UCG-002 decreased in the gut microbiota of mice with CHMACS treatment. Cluster analysis of microbial diversity showed that the above-mentioned differential microbiotas mainly belong to Verrucomicrobia, Spirochaetes, Fusobacteria, Patescibacteria, etc. KEGG and COG annotation suggested that CHMACS increased the abundance of amino acid metabolism and decreased carbohydrate metabolism. It was also confirmed that a strong association exists between changes in the above metabolites, immune cell maturation, and activation. In conclusion, our study reveals that CHMACS kills CC cells by regulating gut microbiota and activating immune cells.